Tertiary-level Students’ Public Speaking Anxiety: A Case Study of English Education Department Students in Indonesia - Siregar, Ayu Meita Puteri (SALEE: Study of Applied Linguistics and English Education, 2022)
Speaking ability is influenced by several factors, one of which is a factor comes from the student, namely the factor self-anxiety. Anxious often appears before, during and after this process of public speaking takes place is a sense of discomfort experienced students. This usually has a bad effect and reduces concentration on the topic being discussed when the anxiety level is getting worse. The aims of this research are to find out the students’ anxiety level, to find the factors that can cause students’ anxiety in public speaking. The instruments of this research were a questionnaire about several problems in public speaking, especially during teaching practices, an interview and documentation. The researcher conducted the research on 6th semester students at the English Education Department, STAIN Mandailing Natal. This study shows the factors of anxiety that make students less proficient in English public speaking, namely; communication apprehension, test anxiety, fear of negative evaluation, and comfort in using English in a public speaking class. The results of this study will contribute to the scope of language teaching in terms of student affective factors, especially self-anxiety factors during language learning.